Effects of nutrient omission and landscape positions on grain sorghum production in northern Ethiopia - Workat Sebnie; Ewunetie Melak; Tilahun Esubalew; Tesfaye Feyisa; Hailu Kendie; Getachew Agegnehu; Gizaw Desta (Agrosystems, Geosciences & Environment)
Abstract Low soil fertility, inappropriate fertilizer application, and low input use are prominent factors contributing to low agricultural productivity in Ethiopia, where soil fertility status varies significantly across the landscape. Applying the correct rate, type, timing, and placement of fertilizers is essential for maximizing agricultural benefits and ensuring sustainable productivity. Addressing these issues is critical for promoting sustainable agricultural practices and improving food security. Therefore, the objective of the experiment was to identify the major yield‐limiting soil nutrients for sorghum yield in northern Ethiopia. A randomized complete block design with three replications was used at each landscape positions. The nutrients evaluated in the study were nitrogen (N), phosphorus (P), sulfur (S), zinc (Zn), boron (B), and potassium (K). The treatment applied included control, recommended NP (RNP), NPSZnB, NPKSZnB, NPZnB, NPSB, NPSZn, 150% NPKSZnB, and 50% NPKSZnB. These treatments were implemented across each landscape position. The research findings indicated that the application of 150% All + K nutrients resulted in the highest grain and biomass yields across all landscape positions. When compared with the RNP treatment, there was no significant difference in yield at all slopes. Omitting S, Zn, B, and K did not significantly affect the grain and biomass yields, suggesting that these nutrients are not yield limiting for sorghum in the study area. These findings suggest that prioritizing N‐ and P‐containing nutrients is essential for maximizing sorghum yield, thus contributing to sustainable agricultural practices and improved food security in the region.